(untitled) (Global Journal of Science Frontier Research, 2025)
This case study presents the comprehensive design and implementation process of major hydraulic components at the Rohin Barrage, including sluice service gates, under sluice service gates, 25T rope drum hoist system, head regulator gates, 15T monorail structure, and stoplog gates. The project addresses complex hydraulic and structural challenges posed by fluctuating river flows, sediment management, and frequent gate operations. The study emphasizes practical design approaches based on relevant IS codes and standards, ensuring functionality, safety, and operational reliability. Through detailed design parameters, componentlevel analysis, and compliance with national standards, this paper serves as a reference for hydraulic gate design and implementation in similar barrage structures.